PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS MAHASISWA DALAM MATA KULIAH PEMBELAJARAN MATEMATIKA KELAS RENDAH - Mukhtar Mukhtar (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
To improve students' understanding of mathematical subjects low grade math learning, it is necessary to use a model of learning that can improve the process of teaching and learning process. One model used is the learning model Contextual Teaching and Learning (CTL). The problems examined in this study is whether the use of the learning model Contextual Teaching and Learning (CTL) can improve student learning outcomes in subjects low grade math learning the academic year 2013-2014 at the University of Sultan Agung Tirtayas Guidance and Counseling Department PGSD. The result is the achievement of students who use learning methods Contextual Teaching and Learning (CTL) is better than the achievement of students who use conventional teaching methods Keywords: Contextual Teaching and Learning (CTL), Learning Mathematics and Mathematical Understanding